Global Immunizations: Health Promotion and Disease Prevention Worldwide. Issue 3 (May 2017) - Macintosh, Janelle L. B.; Eden, Lacey M.; Luthy, Karlen E.; Schouten, Aimee E.
Abstract: Background: Immunizations are one of the most important health interventions of the 20th century, yet people in many areas of the world do not receive adequate immunizations. Approximately 3 million people worldwide die every year from vaccine-preventable diseases; about half of these deaths are young children and infants. Global travel is more common; diseases that were once localized now can be found in communities around the world. Problem: Multiple barriers to immunizations have been identified. Healthcare access, cost, and perceptions of safety and trust in healthcare are factors that have depressed global immunization rates. Interventions: Several global organizations have focused on addressing these barriers as part of their efforts to increase immunization rates. The Bill and Melinda Gates Foundation, The World Health Organization, and the United Nations Children's Emergency Fund each have a part of their organization that is concentrated on immunizations. Clinical Implications: Maternal child nurses worldwide can assist in increasing immunization rates. Nurses can participate in outreach programs to ease the burden of patients and families in accessing immunizations. Nurses can work with local and global organizations to make immunizations more affordable. Nurses can improve trust and knowledge about immunizations in their local communities. Nurses are a powerful influence in the struggle to increase immunization rates, which is a vital aspect of global health promotion and disease prevention. Abstract : Global immunizations save 2.5 million lives per year, yet in many areas of the world, there are low rates of immunizations. Three million people worldwide still die every year from vaccine preventable diseases; about half of those deaths are young children and infants. Barriers to immunizations are presented as well as ongoing work to improve immunization rates worldwide.